Effect of maternal diabetes on fetal heart function on echocardiography: systematic review and meta‐analysis. (1st April 2021) - Depla, A. L.; De Wit, L.; Steenhuis, T. J.; Slieker, M. G.; Voormolen, D. N.; Scheffer, P. G.; De Heus, R.; Van Rijn, B. B.; Bekker, M. N.
ABSTRACT: Objective: Maternal diabetes in pregnancy is associated with structural anomalies of the fetal heart, as well as hypertrophy and functional impairment. This systematic review and meta‐analysis aimed to estimate the effect of maternal diabetes on fetal cardiac function as measured by prenatal echocardiography. Methods: We performed a search of the EMBASE, PubMed and The Cochrane Library databases, from inception to 4 July 2019, for studies evaluating fetal cardiac function using echocardiography in pregnancies affected by diabetes compared with uncomplicated pregnancies. Outcome measures were cardiac hypertrophy and diastolic, systolic and overall cardiac function as assessed by various ultrasound parameters. The quality of the studies was assessed using the Newcastle–Ottawa Scale. Data on interventricular septal (IVS) thickness, myocardial performance index (MPI) and E/A ratio were pooled for the meta‐analysis using random‐effects models. For pregnancies with diabetes, results were reported overall and according to whether diabetes was pregestational (PDM) or gestational (GDM). Results were also stratified according to the trimester in which fetal cardiac assessment was performed. Results: Thirty‐nine studies were included, comprising data for 2276 controls and 1925 women with pregnancy affected by diabetes mellitus (DM). Of these, 1120 had GDM, 671 had PDM and in 134 cases diabetes type was not specified. Fetal cardiac hypertrophy was more prevalent in diabetic pregnancies than in non‐diabetic controls in 21/26 studies, and impaired diastolic function was observed in diabetic pregnancies in 22/28 studies. The association between DM and systolic function was inconsistent, with 10/25 studies reporting no difference between cases and controls, although more recent studies measuring cardiac deformation, i.e. strain, did show decreased systolic function in diabetic pregnancies. Of the studies measuring overall fetal cardiac function, the majority (14/21) found significant impairment in diabetic pregnancies. Results were similar when stratified according to GDM or PDM. These effects were already present in the first trimester, but were most profound in the third trimester. Meta‐analysis of studies performed in the third trimester showed, compared with controls, increased IVS thickness in both PDM (mean difference, 0.75 mm (95% CI, 0.56–0.94 mm)) and GDM (mean difference, 0.65 mm (95% CI, 0.39–0.91 mm)) pregnancies, decreased E/A ratio in PDM pregnancies (mean difference, –0.09 (95% CI, –0.15 to –0.03)), no difference in E/A ratio in GDM pregnancies (mean difference, –0.01 (95% CI, –0.02 to 0.01)) and no difference in MPI in either PDM (mean difference, 0.04 (95% CI, –0.01 to 0.09)) or GDM (mean difference, 0.03 (95% CI, –0.01 to 0.06)) pregnancies. Conclusions: The findings of this review show that maternal diabetes is associated with fetal cardiac hypertrophy, diastolic dysfunction and overall impaired myocardial performance on prenatal ultrasound, irrespective of whether diabetes is pregestational or gestational. Further studies are needed to demonstrate the relationship with long‐term outcomes. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.